Post-conflict justice in divided democracies: the 1984 anti-Sikh riots in India. Issue 6 (2nd June 2020) - Jeffery, Renée; Hall, Ian
Abstract: Official figures claim that almost 3000 people were killed, and many more injured or displaced, in four days of rioting aimed at the Sikh population of Delhi in late October and early November 1984 following the assassination of Indira Gandhi. This article analyses the efforts made to address the human rights violations that occurred. It argues that as a divided democracy, India has struggled to do justice to the victims, despite multiple commissions of inquiry, compensation schemes and a prime ministerial apology. It argues that this has occurred not simply because of challenges commonly faced by democracies dealing with similar incidents, but also because of the particular problems faced in a context in which we see continuity of rule by a political elite allegedly implicated in the abuse and in which there is acute concern for the survival of a fragile divided polity.